RHEUMATOID ARTHRITIS: THE IMPORTANCE OF EVIDENCE BASED DIAGNOSTIC REASONING IN PREVENTING DEBILITATING CONSEQUENCES - Gul, Naheed; Quadri, Mujtaba (Journal of Ayub Medical College Abbottabad, 2014)
Background: The early diagnosis of Rheumatoid arthritis can improve clinical outcomes, in terms of morbidity and mortality. This study evaluates the role of evidence informed diagnostic reasoning in the early diagnosis of Rheumatoid arthritis. Methods: A cross-sectional survey was conducted on 200 respondents inclusive of doctors and medical students, at Shifa college of Medicine, Islamabad from April to December 2010. A questionnaire with three common clinical scenarios of low, intermediate and high pre-test probability for rheumatoid arthritis (RA) was provided to the respondents. The differences between the reference and respondents’ estimates of pre and post-test probability were used to assess the respondents’ clinical diagnostic reasoning process, as a tool to diagnose RA early. Respondents were also enquired about the cost effectiveness or potential harms of Rheumatoid factor (RF). Consecutive sampling technique was used and the data was analysed using SPSS-15. Results: In all scenarios, the pre-test probability was estimated close to the reference estimates suggesting respondents’ ability to rule in or rule out the disease. However, some over-estimation of the pre-test probability was noticed in low and intermediate pre-test probability settings. Post-test probabilities were significantly underestimated reflecting their inability to calculate post-test probabilities in all scenarios. More tests were ordered as the disease probability increased. Most respondents were of the opinion that RF is cost effective and safe. Conclusions: The significant underestimation of the post-test probability necessitates more emphasis on Bayesian probabilistic thinking in clinical practice to facilitate early diagnosis of rheumatoid arthritis. Keywords: Rheumatoid arthritis. Rheumatoid factor, Probability, Early diagnosis